Profitabilitas Perusahaan Dilihat dari Perputaran Kas, Perputaran Piutang dan Piutang Tak Tertagih - Jordan, Vicky; Lilia, Wirda (Jurnal Pendidikan Ekonomi Undiksha, 2020)
In the financial sector, cash turnover, accounts receivable turnover and accounts receivable turnover are very important to the profitability of a company. In this case, the company must implement a system to control receivables and also ensure that credit sales are carried out effectively and efficiently so that receivables do not turn into bad debt so that both sales and profits can increase. For this reason, it is necessary to control receivables at PT. PAP to ensure all receivables are paid on time. PT. PAP uses a third party, namely leasing for the accounts receivable process. The research approach used is quantitative research and the type of research used is descriptive research. The source of the data in this study is the secondary population data used in this study, namely all financial statements of PT. PAP obtained a sample of 60 months in 5 years (2014-2018). The coefficient of determination in this study was 80.4%, the remaining 19.6% was explained by other variables outside the study. The results of the study are based on multiple linear regression models and hypothesis testing using the f test and t test. Cash turnover, accounts receivable turnover and uncollectible receivables have a positive and significant effect on profitability at PT. PAP